Potassium Fulvate for Improving Nutrient Status, Photosynthesis, and Agronomic Traits of Maize. Issue 13 (20th July 2022) - Ngennoy, Supanun; Jompuk, Choosak; Thongjoo, Chaisit; Sonjaroon, Weerasin; Chindaphan, Kanokporn; Jutamanee, Kanapol
ABSTRACT: Potassium fulvate (KF) is salt form of fulvic acids and has a functional role to improve plant growth and soil quality. Its response under reduced soil fertility is less reported, particularly in sand soil. We examined the beneficial effects of KF derived from leonardite when used with chemical fertilizers (CF) on maize's nutrient status, photosynthetic and agronomic traits in sand soil. KF, often extracted from leonardite, was applied to maize seedlings in four treatments. Composition and functional groups of KF found in leonardite were similar to fulvic acids extracted from other sources, and resulted in nutrient adsorption such as potassium (K), calcium (Ca), magnesium (Mg), manganese (Mn), zinc (Zn), and copper (Cu) uptake in shoot. Applying KF with CF enhanced the physiological and growth traits as well as biomass of maize compared to the application of CF alone. Further, KF with 75% CF produced results comparable to that of 100% CF alone. KF improved plant nutrition, enhanced photosynthetic parameters and growth traits, and increased the biomass of maize when CF application was reduced by 25% from the recommended amount. Thus, the application of KF with CF is the practical guideline for using CF for maize production in low fertility sand soil conditions.